Prof. John Mansour: to be a good surgical oncologist, you can’t be just one thing - Lin, Teresa; Gao, Skylar (Digestive Medicine Research, 2018)
Dr. Mansour (Figure 1) is the Chief of the Division of Surgical Oncology at UT Southwestern Medical Center and Associate Professor of Surgery. He is also a surgical oncologist on the nationally recognized gastrointestinal cancer team at UT Southwestern Medical Center’s Simmons Comprehensive Cancer Center.